Exogenous Calcium Alleviates Nocturnal Chilling-Induced Feedback Inhibition of Photosynthesis by Improving Sink Demand in Peanut (Arachis hypogaea) - Wu, Di; Liu, Yifei; Pang, Jiayin; Yong, Jean Wan Hong; Chen, Yinglong; Bai, Chunming; Han, Xiaori; Liu, Xinyue; Sun, Zhiyu; Zhang, Siwei; Sheng, Jing; Li, Tianlai; et al. (Frontiers in Plant Science, 2020)
Arachis hypogaea (peanut) is a globally important oilseed crop with high nutritional value. However, upon exposure to overnight chilling stress, it shows poor growth and seedling necrosis in many cultivation areas worldwide. Calcium (Ca2+) enhances chilling resistance in various plant species. We undertook a pot experiment to investigate the effects of exogenous Ca2+ and a calmodulin inhibitor on growth and photosynthetic characteristics of peanut exposed to low night temperature (LNT) stress following warm sunny days. The LNT stress reduced growth, leaf extension, biomass accumulation, gas exchange rates, and photosynthetic electron transport rates. Following LNT stress, we observed larger starch grains and a concomitant increase in nonstructural carbohydrates and hydrogen peroxide concentrations. The LNT stress further induced photoinhibition and caused structural damage to the chloroplast grana. Exogenous Ca2+ enhanced plant growth following LNT stress, possibly by allowing continued export of carbohydrates from leaves. Foliar Ca2+ likely alleviated the nocturnal chilling-dependent feedback limitation on photosynthesis in the daytime by increasing sink demand. The foliar Ca2+ pretreatment protected the photosystems from photoinhibition by facilitating cyclic electron flow and decreasing the proton gradient across thylakoid membranes during LNT stress. Foliar application of a calmodulin inhibitor increased the negative impact of LNT stress on photosynthetic processes, confirming that Ca2+–calmodulin played an important role in alleviating photosynthetic inhibition due to the overnight chilling-dependent feedback.